AN OVERVIEW OF THE RISK FACTORS FOR PREECLAMPSIA IN WOMEN WITH A HISTORY OF PREECLAMPSIA IN PREVIOUS PREGNANCIES IN JEMBER AGRICULTURAL AREA - Septinia Anggraita; Dini Kurniawati; Eka Afdi Septiyono (UPT Penerbitan Universitas Jember, 2023)
Introduction: Preeclampsia is a condition where symptoms appear in the third trimsemester of pregnant women. Preeclampsia has the main symptoms of edema, hypertension, and proteinuria, called the triad of preeclampsia. Preeclampsia is accompanied by complications such as seizures that can lead to eclampsia. Signs that can be seen are systolic blood pressure below 160 mmHg and diastolic blood pressure belom 110 mmHg. Preeclampsia is a problem in Indonesia, especially Jember, which causes high MMR (Maternal Mortality Rate) in Indonesia. Purpose: This study aims to determine risk factors that can cause preeclampsia, such as taking antihypertensive drugs, length of last pregnancy, history of gestational hypertension, age of first gestational hypertension, signs and symptoms of preeclampsia during pregnancy, signs and symptoms of preeclampsia before first pregnancy. Methods: This research is quantitative, with the number of respondents as many as 150 pregnant women. Questionnaires will be distributed to respondents in the form of Google Forms. Result: As a result, 23 respondents had preeclampsia, and the rest had risk factors for preeclampsia. Conclusion: The results of this study are used to provide preventive measures for pregnant women to reduce MMR in Indonesia, especially in Jember.